Effects of ethnicity and marital status on mortality in Singapore - Boey, Jeremy Chee Mun (2008)
This report attempts to investigate the interaction effects between social demography and mortality in Singapore, in particular ethnicity and marital status. Using the Census Method, mortality rates were computed for the various groups under investigations.